FUNGSI KALIGRAFI ARAB SEBAGAI MEDIA DAKWAH VISUAL DI MASYARAKAT MUSLIM MODERN - Qothrunnadha Qothrunnadha; Muhammad Arif Billah; Ulil Albab; Muhammad Fikri Al-Mujaki; Dzulfaqor Daffa; Muhammad Mukti Adli; Sultan Yazid; Minatur Rokhim (Yayasan Haiah Nusratul Islam, 2025)
Arabic calligraphy is one form of Islamic art that not only contains high aesthetic value, but is also full of spiritual messages. In the context of modern Muslim society, Arabic calligraphy is not only found in places of worship, but also in digital media, popular culture products, and public spaces. This study aims to examine the function of research using a descriptive qualitative approach through library studies and observations of visual da'wah media that utilize calligraphy. The results of the study show that Arabic calligraphy functions as a means of reminding Islamic values, strengthening the visual identity of Islam, and a bridge of communication for da'wah that is authentic in the digital era.